The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1073/pnas.0802515105
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution distance mapping in rhodopsin reveals the pattern of helix movement due to activation

Abstract: Site-directed spin labeling has qualitatively shown that a key event during activation of rhodopsin is a rigid-body movement of transmembrane helix 6 (TM6) at the cytoplasmic surface of the molecule. To place this result on a quantitative footing, and to identify movements of other helices upon photoactivation, double electron-electron resonance (DEER) spectroscopy was used to determine distances and distance changes between pairs of nitroxide side chains introduced in helices at the cytoplasmic surface of rho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
454
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(494 citation statements)
references
References 45 publications
34
454
0
2
Order By: Relevance
“…To distinguish between the different submodels will require other, more structure sensitive time-resolved spectral techniques. The scheme presented here, however, is consistent with EPR studies describing the helix-6 movement involved in activation, 31 and G-protein peptide mimic binding studies. 41 Many structural studies reveal complex helix movements involving the rearrangements of H-bonding in the transmembrane region of the protein, and several states of the chromophore relaxation during activation.…”
Section: ■ Conclusionsupporting
confidence: 85%
See 1 more Smart Citation
“…To distinguish between the different submodels will require other, more structure sensitive time-resolved spectral techniques. The scheme presented here, however, is consistent with EPR studies describing the helix-6 movement involved in activation, 31 and G-protein peptide mimic binding studies. 41 Many structural studies reveal complex helix movements involving the rearrangements of H-bonding in the transmembrane region of the protein, and several states of the chromophore relaxation during activation.…”
Section: ■ Conclusionsupporting
confidence: 85%
“…As expected, the ratio of the Meta Ib 480 formation of Meta Ib 480 and the enhanced deprotonation leading to the formation of Meta IIb to the helix-6 movement observed by EPR on a similar time scale. 28,31 This helix movement is necessary for G-protein binding. It is also suggested that the proton uptake by the protein, leading to its active state and causing the anomalous pH dependence of the equilibrium between Meta I and Meta II in Scheme 1, is initiated by the helix movement.…”
Section: ■ Discussionmentioning
confidence: 99%
“…31 In the activation-related scenario, TMH6 undergoes the most important movement where the kink functions as a pivot and finally leads to G-protein coupling and activation. 32,33 Substitution of the proline is expected to lead to modifications in the signaling properties by causing changes in the helix conformation, intramolecular interactions and thereby the helix arrangement. This is supported by recent findings regarding corresponding prolines in other glycoprotein hormone receptors, the thyrotropin receptor (hTSHR, Pro639), 34 and the lutropin/choriogonadotropin receptor (rLHCGR, Pro588).…”
Section: Fsh Resistance Associated With a T(2;8)mentioning
confidence: 99%
“…The helix movement also results in a pH-dependent protonation of glutamate 134. 14,18,19 Previous studies of the human rhodopsin attempted to characterize human rhodopsin intermediates using both temperature trapping and time-resolved spectroscopic measurements to determine the similarities and differences between the activation of human and bovine rhodopsins. 20,21 It was expected that differences in the sequences of human and bovine rhodopsins in the connection from transmembrane 5 and extracellular loop 2 could affect rhodopsin activation and G-protein binding.…”
Section: R Hodopsin Is a G-protein-coupled Receptor (Gpcr) Foundmentioning
confidence: 99%